2021
DOI: 10.3390/ijms22169052
|View full text |Cite
|
Sign up to set email alerts
|

Nitro-Oleic Acid (NO2-OA) Improves Systolic Function in Dilated Cardiomyopathy by Attenuating Myocardial Fibrosis

Abstract: Nitro-oleic acid (NO2-OA), a nitric oxide (NO)- and nitrite (NO2−)-derived electrophilic fatty acid metabolite, displays anti-inflammatory and anti-fibrotic signaling actions and therapeutic benefit in murine models of ischemia-reperfusion, atrial fibrillation, and pulmonary hypertension. Muscle LIM protein-deficient mice (Mlp−/−) develop dilated cardiomyopathy (DCM), characterized by impaired left ventricular function and increased ventricular fibrosis at the age of 8 weeks. This study investigated the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Therefore, in yeast, only OA or PA would be available to react with RNS to generate the corresponding NO 2 -FAs. We searched nitrated oleic acid because this molecule had been detected in other species, and its implications in cell signaling processes had been previously described [52][53][54][55][56]. In line with this, the NO 2 -OA levels in S. cerevisiae in the non-stress situation were 0.038 ± 0.01 pmoles/g FW, which fall within the range with the concentration of other signaling molecules.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, in yeast, only OA or PA would be available to react with RNS to generate the corresponding NO 2 -FAs. We searched nitrated oleic acid because this molecule had been detected in other species, and its implications in cell signaling processes had been previously described [52][53][54][55][56]. In line with this, the NO 2 -OA levels in S. cerevisiae in the non-stress situation were 0.038 ± 0.01 pmoles/g FW, which fall within the range with the concentration of other signaling molecules.…”
Section: Discussionmentioning
confidence: 55%
“…Human atherosclerosis is a typical vessel-derived disease, so NO 2 -FAs could be an alternative therapy in that case. NO 2 -OA has also been reported by Braumann et al that can attenuate myocardial fibrosis in a murine model of dilated cardiomyopathy (DCM) [37].…”
Section: -Nitro Oleic Acid (Cxa-10) and Its Derivatives As Anti-inflammatory And Cytotoxic Agentsmentioning
confidence: 75%
“…In the PREDIMED trial conducted by Guasch-Ferré et al MUFA intake was found to have a significant correlation with total cardiovascular disease (CVD) risk as a protective factor (HR = 0.630, 95%CI: 0.430–0.940) ( 38 ). This protection may be mediated by the synthesis of the endogenous signaling mediator NO 2 -OA ( 17 ) and hydroxylation to hydroxyl fatty acids in response to metabolic disturbances and increased inflammatory stress in the DCM ( 17 ). In general, these positive correlation results are consistent with ours, suggesting the causal effect of oleic acid on DCM.…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings of DCM metabolomics studies, linoleic acid could be used as the primary biomarker to measure the effectiveness of DCM treatment, and hydroxyl fatty acid esters were potential biomarkers to identify DCM ( 16 ). Additionally, Nitro-oleic acid (NO 2 -OA), a signaling mediator produced naturally by reacting oleic acid with nitrogen dioxide (NO 2 ), was created as a therapeutic agent for fibrotic and inflammatory diseases and has been proven effective in numerous animal models of cardiovascular diseases ( 17 ). Controversially, several in vitro and animal investigations have raised concerns that linoleic acid and other n-6 PUFAs may induce inflammation and thrombosis ( 18 ).…”
Section: Introductionmentioning
confidence: 99%